Budget funds as a subject of criminal offenses - Topchii, Vasyl Vasylovych; Mamka, Hryhorii Mykolaiovych (Університет ДФС України, 2020)
Today, in the context of inconsistent reforms of market relations, the use of budget and banking systems, which are characterized by a large concentration of funds in both cash and non-cash forms, different financial services and tools with different levels of protection and liquidity, with great customer potential, which is constantly increasing and changing. According to estimates of international companies and directly the auditing company "Price Waterhouse Coopers", the annual loss in the field of public finance by European countries from such criminal offenses is about $ 33 billion.

Сьогодні, в умовах непослідовних реформ ринкових відносин, використання бюджетної та банківської систем, які характеризуються великою концентрацією коштів як у готівковій, так і в безготівковій формі, різноманітних фінансових послуг та інструментів з різним рівнем захисту та ліквідності , з великим клієнтським потенціалом, який постійно збільшується та змінюється. За оцінками міжнародних компаній і безпосередньо аудиторської компанії «Price Waterhouse Coopers», щорічні збитки у сфері державних фінансів європейських країн від подібних кримінальних злочинів становлять близько 33 мільярдів доларів.
Keywords: Budget funds; criminal legislation; criminal offenses; Criminal code of Ukraine; Бюджетні кошти; кримінальне законодавство; кримінальні правопорушення; Кримінальний кодекс України